Forever more - Johnson, Puff, Ewanya Johnson; Walden, Narada Michael; Sony Music Entertainment (Santa Monica, California : Sony Music Entertainment, 1996)
Contains the single taken from the album Miracle.
CD 1 : Single / (4:01) -- Album version / (5:05).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English